World Trade Center exposure, post‐traumatic stress disorder, and subjective cognitive concerns in a cohort of rescue/recovery workers. (23rd December 2019) - Singh, A.; Zeig‐Owens, R.; Hall, C. B.; Liu, Y.; Rabin, L.; Schwartz, T.; Webber, M. P.; Appel, D.; Prezant, D. J.
Abstract : Objective: To determine whether World Trade Center (WTC)‐exposure intensity and post‐traumatic stress disorder (PTSD) are associated with subjective cognitive change in rescue/recovery workers. Method: The population included 7875 rescue/recovery workers who completed a subjective cognition measure, the Cognitive Function Instrument (CFI), between 3/1/2018 and 2/28/2019 during routine monitoring, indicating whether they had experienced cognitive and functional difficulties in the past year. Higher scores indicated greater self‐perceived cognitive change. Probable PTSD, depression, and alcohol abuse were evaluated by validated mental health screeners. Logistic regression assessed the associations of WTC exposure and current PTSD with top‐quartile (≥2) CFI score, and of early post‐9/11 PTSD with top‐quartile CFI in a subpopulation ( N = 6440). Models included demographics, smoking, depression, and alcohol abuse as covariates. Results: Mean age at CFI completion was 56.7 ± 7.7 (range: 36–81). Participants with high‐intensity WTC exposure had an increased likelihood of top‐quartile CFI score (odds ratio[OR] vs. low exposure: 1.32, 95%CI: 1.07–1.64), controlling for covariates. Current and early PTSD were both associated with top‐quartile CFI (OR: 3.25, 95%CI: 2.53–4.19 and OR: 1.56, 95%CI: 1.26–1.93) respectively. Conclusions: High‐intensity WTC exposure was associated with self‐reported cognitive change 17 years later in rescue/recovery workers, as was PTSD. Highly WTC‐exposed subgroups may benefit from additional cognitive evaluation and monitoring of cognition over time.